Efektivitas Cognitive Behavior Therapy dalam Pemulihan Pasien Skizofrenia: Scoping Review - Putri, Ni Komang Suasti Puspita; Herdiyanto, Yohanes K. (Flourishing Journal, 2025)
Cognitive Behavioral Therapy (CBT) is a psychotherapy approach that has been proven effective and commonly used in the treatment of schizophrenia, particularly in supporting mental recovery and improving patients' daily functioning. This study aims to examine the effectiveness of CBT in supporting the recovery process of schizophrenia patients in Indonesia. The method used is a scoping review with a systematic search conducted across Google Scholar, ResearchGate, and Garuda. A total of ten articles that met the inclusion criteria were further analyzed. The results of the review show that CBT has a positive impact on five key aspects of recovery: reduction of hallucinations, decrease in aggressive behavior, improvement in self-esteem, restructuring of maladaptive thinking patterns, and reduction of anxiety and depressive symptoms. The effectiveness of CBT is more effective when combined with supportive therapies such as muscle relaxation, drawing therapy, and social skills training. Although the findings are promising, this review also highlights the limited number of local studies and emphasizes the need for cultural adaptation in the Indonesian context. Therefore, CBT is considered a promising intervention that should be further developed by incorporating cultural values and involving families and healthcare professionals to support sustainable recovery among schizophrenia patients. AbstrakCognitive behavioral therapy (CBT) adalah pendekatan psikoterapi yang terbukti efektif dan sering digunakan dalam menangani skizofrenia, terutama untuk membantu pemulihan kondisi mental dan kemampuan fungsi sehari-hari pasien. Penelitian ini bertujuan untuk mengkaji efektivitas CBT dalam mendukung proses pemulihan pasien skizofrenia di Indonesia. Metode yang digunakan adalah scoping review melalui pencarian sistematis pada tiga basis data daring, yaitu Google Scholar, ResearchGate, dan Garuda. Sebanyak sepuluh artikel yang memenuhi kriteria inklusi dianalisis lebih lanjut. Hasil kajian menunjukkan bahwa CBT memberikan dampak positif pada lima aspek utama pemulihan, yaitu pengurangan halusinasi, penurunan perilaku agresif, peningkatan harga diri, restrukturisasi pola pikir maladaptif, serta penurunan gejala kecemasan dan depresi. Efektivitas CBT juga meningkat ketika dikombinasikan dengan terapi pendukung seperti relaksasi otot, terapi menggambar, dan pelatihan sosial. Meskipun hasilnya menjanjikan, kajian ini juga menemukan keterbatasan dalam jumlah studi lokal dan perlunya penyesuaian terhadap konteks budaya Indonesia. Oleh karena itu, CBT dinilai sebagai intervensi yang potensial dan layak di kembangkan lebih lanjut dengan mempertimbangkan nilai budaya, serta melibatkan keluarga dan tenaga kesehatan untuk mendukung keberlanjutan proses pemulihan pasien skizofrenia.